Figurative Language in Taylor Swift’s Song Lyrics “All Too Well" in a 10-Minute Version - Olivia Deviani; Hendar Hendar (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
The purposes of this research to find the types of figurative language and to uncover the types of meaning used in the ten minutes song lyrics by Taylor Swift. The research method used is qualitative descriptive method and to collect the data needed, the library research is implemented. The main theories used in this research are the theory of figurative language by Kennedy (1979) and of meaning types by Leech (1981). The result of the research shows respectively that there are 29 data of figurative language found in the lyrics of Taylor Swifts’ song comprising of 10 data (34.5%) on metaphor, 6 data (20.7%) on personification, 5 data (17.2%) on simile, 2 data (6.9%) on symbol, 2 data (6.9%) on hyperbole), 3 data (10.3%) on irony, 1 data (3.5%) on metonymy, but no data (0%) on allision; whereas the data on types of meaning found in the lyrics of Taylor Swifts’ song are 18 data (65.5%) on connotative meaning, 8 data (24.2%) on affective meaning and 3 data (10.3%) on conceptual meaning. The figurative language metaphor (34.5%) and connotative meaning (24.2%) become the most dominant due to the fact that Swift invites the listener to interpret and feel the emotions more intensely, creating a more immersive and evocative listening experience. Other than that, the song lyrics describe the feeling of how painful after breakup and severe betrayal.